Literature Review: Analysis of Pregnant Women's Compliance with Multiple Micronutrient Supplement (MMS) Consumption (Interviewed from the Health Belief Model Theory and Theory of Planned Behavior) - Yulida Mufidah; Herawati Herawati; Hardyan Sauqi; Meitria Syahadatina Noor; Fauzie Rahman (Indonesian Journal of Global Health Research, 2025)
Nutritional deficiencies in pregnant women, such as anemia and KEK, are serious public health issues that can lead to complications such as low birth weight and premature birth. To address this problem, the WHO recommends MMS as an alternative or supplement to iron and folic acid supplements, as MMS contains a combination of 15 essential vitamins and minerals, making it a more comprehensive intervention. Although Indonesia has gradually launched the MMS program since 2024, the level of compliance with supplement consumption is still low, influenced by a lack of knowledge, cultural values, and discomfort such as taste and tablet size. This study aims to analyze the factors that influence MMS consumption compliance using the Health Belief Model and Theory of Planned Behavior frameworks. The research method used is a literature review by searching national and international journals published between 2020 and 2025 with the keyword "Adherence with Multiple Micronutrient Supplement (MMS) Consumption by Pregnant Women." Compliance is greatly influenced by a combination of psychological and contextual factors. The initial data consisted of 207 journals, then analyzed according to the characteristics and 10 suitable articles were found. The literature review was conducted narratively by searching for scientific articles from databases relevant to the research topic, then analyzed descriptively and comparatively. According to the Health Belief Model, the main driver of compliance is the mother's belief, particularly her perception of the benefits; mothers believe that MMS provides real benefits. Meanwhile, the Theory of Planned Behavior highlight the role of perceived behavioral control, which is the mother's view of the ease of acting consistently.